Reciprocity? International Preceptors' Perceptions of Global Health Elective Learners at African Sites - Elizabeth M. Keating; Heather Haq; Chris A. Rees; Padma Swamy; Teri L. Turner; Stephanie Marton; Jill Sanders; Edith Q. Mohapi; Peter N. Kazembe; Gordon E. Schutze (Ubiquity Press, 2019)
Background: Short-term global health electives (STGHEs) have become increasingly common, with evidence showing educational and clinical benefits for short-term learners (STLs). Despite increased recognition that STGHEs should be mutually beneficial for host sites and STLs, evidence demonstrating the impact on international host preceptors is lacking. Objectives: To understand international host preceptors' perceptions regarding benefits and burdens of hosting STLs. Methods: Focus group discussions with a convenience sample of 10 of 18 eligible preceptors were conducted at pediatric STGHE sites in Malawi and Lesotho. Qualitative content analysis was performed to identify themes using a deductive-inductive approach. Findings: Common themes regarding benefits to preceptors included increased knowledge and resources for learning from STLs, broadened differential diagnoses, and the satisfaction of teaching. Regarding burdens, preceptors perceived that supervising STLs decreases efficiency. Preceptors identified the burden of having to intervene in instances that could lead to patient harm. Some preceptors perceived that STLs under-valued preceptors' clinical decision-making in resource-limited contexts. Conclusions: Our findings emphasize the need for institutions to identify mutuality of benefits between STLs and host sites when developing STGHEs. Host preceptors identified robust pre-departure training for STLs, lengthened duration of STGHEs, and formal preceptor orientation as ways to enhance mutuality of benefits.